Universal Health Coverage in Pakistan: Challenges, Reforms, and the Road to 2030 - Babar Tasneem Shaikh (Annals of Global Health, 2026)
Background: Universal Health Coverage (UHC) aims to ensure that all individuals have access to essential health services without financial hardship. Pakistan, despite constitutional commitments and policy reforms, faces significant hurdles in progressing toward this global goal due to systemic, structural, and socioeconomic challenges. Methods: This narrative review synthesizes available literature, policy documents, and programmatic evidence to examine Pakistan’s preparedness for UHC. The analysis is structured around four thematic levels: policy, institutional, population, and service delivery, identifying barriers and opportunities within each domain. Findings: At the policy level, political instability, inadequate financing (